Possible Sarcopenia and Impact of Dual-Task Exercise on Gait Speed, Handgrip Strength, Falls, and Perceived Health - Merchant, Reshma Aziz; Chan, Yiong Huak; Hui, Richard Jor Yeong; Lim, Jia Yi; Kwek, Sing Cheer; Seetharaman, Santhosh K.; Au, Lydia Shu Yi; Morley, John E. (Frontiers in Medicine, 2021)
Background: Sarcopenia is defined as a progressive age-related loss in muscle mass and strength affecting physical performance. It is associated with many negative outcomes including falls, disability, cognitive decline, and mortality. Protein enriched diet and resistance training have shown to improve muscle strength and function but there is limited evidence on impact of dual-task exercise in possible sarcopenia. Objective: To evaluate impact of community-based dual-task exercise on muscle strength and physical function in possible sarcopenia defined by either slow gait (SG) or poor handgrip strength (HGS). The secondary aims include effect on cognition, frailty, falls, social isolation and perceived health. Methods: Community-dwelling older adults ≥ 60 years old were recruited from screening program intended to identify seniors at risk, and invited to participate in dual-task exercise program called HAPPY (Healthy Ageing Promotion Program for You). One hundred and eleven participants with possible sarcopenia completed 3 months follow-up. Questionnaire was administered on demographics, frailty, sarcopenia, falls, perceived health, social network, functional and cognitive status. Physical performance included assessment of HGS, gait speed and Short Physical Performance Battery test (SPPB). Results: The mean age of the Exercise group was 75.9 years old and 73.0% were women. The Exercise group had more female (73.0% vs 47.5%), were older (75.9 vs 72.5years old), had higher prevalence of falls (32.4% vs 15.0%), lower BMI (23.7 vs 25.8) and education (4.0 vs 7.2 years). The gait speed of the Exercise group increased significantly with significant reduction in the prevalence of SG and poor HGS. All components of SPPB as well as the total score increased significantly while the prevalence of pre-frailty and falls dropped by half. The risk of social isolation reduced by 25% with significant improvement in perceived health and cognition in the Exercise group. Significant impact on improvement gait speed persisted after adjustment for baseline factors. Conclusion: Dual-task exercise program is effective in improving gait speed and reducing the prevalence of poor HGS with significant improvement in perceived health, cognition and reduction in falls and frailty. Future prospective randomised control trial is needed to evaluate the effectiveness of dual-task interventions in reversing sarcopenia.